Perbedaan Profil Protein Plasma Darah Mencit Menggunakan SDS-PAGE Tanpa Penambahan dan dengan Penambahan 2-Mercaptoethanol - Khaerunissa Anbar Istiadi; Iffa Afiqa Khairani; Silvia Andriani (Universitas Pendidikan Ganesha, 2024)
SDS-PAGE is a method used to analyze proteins based on differences in molecular weight. Sample preparation in SDS-PAGE with 2-mercaptoethanol will reduce disulfide bonds in proteins. The sulfide bond reduction process will cause differences in protein conformation and profile. The purpose of this study was to compare the pattern of blood plasma protein profiles of mice analyzed using SDS-PAGE, with the addition of 2-mercaptoethanol and without the addition of 2-mercaptoethanol in a mixture of sample buffer solutions. The results of SDS-PAGE showed that the blood plasma protein profile of mice without the addition and with the addition of 2-mercaptoethanol showed differences in the number of protein bands, the molecular weight of several proteins and the thickness of the protein bands. There were nine protein bands with a molecular weight above 52 kDa in the profile without the addition of 2-mercaptoethanol, while there were only five protein bands with a molecular weight above 52 kDa in the profile with the addition of 2-mercaptoethanol. The difference in protein profile patterns shows that mouse blood plasma contains proteins containing disulfide bonds that can be reduced by 2-mercaptoethanol.